Agreements and controversies of national guidelines for bronchiolitis: Results from an Italian survey - Sara Manti; Amelia Licari; Ilaria Brambilla; Carlo Caffarelli; Mauro Calvani; Fabio Cardinale; Giorgio Ciprandi; Claudio Cravidi; Marzia Duse; Alberto Martelli; Domenico Minasi; Michele Miraglia Del Giudice; et al. (Immunity, Inflammation and Disease)
Abstract Introduction Significant variations in the management of bronchiolitis are often recorded, and, in parallel, to recommend a univocal clinical approach is challenging and still questioned. This study is aimed to evaluate the diagnostic and therapeutic management of bronchiolitis in children adopted by Italian pediatricians following the national guidelines. Material and Methods A survey study was designed and carried out by sending an email an open‐ended questionnaire developed by an expert panel of the Scientific Board of the Italian Society of Pediatric Allergology and Immunology (SIAIP). Questions were designed according to the national intersociety consensus document on treatment and prevention of bronchiolitis in newborns and infants. Results Overall, 234 pediatricians were taking part in the study. When diagnosing bronchiolitis, only 44.01% (103/234) of participants correctly followed the national guidelines. All participants (100%) would perform laboratory tests and/or radiological exams. 44.01% administered oxygen (O2) when O2 saturation was minor than 92%. About the therapeutic regimen, marked discrepancies between national guidelines and recorded answers were reported. Indications for hospital admission and discharge criteria were in line with the national guidelines. Conclusions There is a significant practice variation in the management of acute bronchiolitis among Italian physicians. Some wrong attitudes need to be further discouraged, such use of diagnostic procedures and therapeutic approaches. Further research is urgently required to define the best management of patients with bronchiolitis and implement strategies to standardize care and improve the quality of care.